2019
DOI: 10.4102/sajhivmed.v20i1.963
|View full text |Cite
|
Sign up to set email alerts
|

Baseline CD4 and mortality trends in the South African human immunodeficiency virus programme: Analysis of routine data

Abstract: Background Despite widespread availability of antiretroviral therapy (ART) in South Africa, there remains a considerable burden of human immunodeficiency virus (HIV)-related morbidity and mortality. Objectives To describe ART initiation and outcome trends over time, with a focus on clients presenting with advanced HIV-infection, so as to identify interventions to reduce morbidity and mortality. Methods Routine TIER.Net data from HIV-infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
1
17
1
Order By: Relevance
“…Prior to the introduction of test–and–treat, this algorithm worked well for estimating incidence as the guideline at the time recommended delayed ART initiation. While the scale up of test and treat has been a major breakthrough and an important intervention globally, as the number of individuals who initiate ART in the early stage of their infection increases with the scale up of test and treat, clinical criteria such as viral load and ART can no longer accurately differentiate recent infections from long–term infections [ 41 , 42 ]. The PMTCT programme, in particular, has high ART coverage [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the introduction of test–and–treat, this algorithm worked well for estimating incidence as the guideline at the time recommended delayed ART initiation. While the scale up of test and treat has been a major breakthrough and an important intervention globally, as the number of individuals who initiate ART in the early stage of their infection increases with the scale up of test and treat, clinical criteria such as viral load and ART can no longer accurately differentiate recent infections from long–term infections [ 41 , 42 ]. The PMTCT programme, in particular, has high ART coverage [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported a 20% ART deferral rate among ART eligible patients diagnosed under the CD4 < 350 policy [ 21 ]. Although the proportion of participants diagnosed with CD4 > 350 was marginally higher during the SDI policy than under previous ART guidelines; the majority still test at CD4 counts below 350 cell/µl [ 42 ]. The reduced dependence on CD4 test results for ART initiation under the UTT and SDI policies may have inadvertently resulted in a reduced availability of baseline CD4 results, as nearly half of the participants were missing baseline CD4 data in their clinic files [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is concerning that low baseline CD4 is significantly associated with immunological non-response, as a notable proportion of patients initiating ART in South Africa do so with low CD4 counts. 2 In particular, older patients and males are more likely to present late for HIV care with low baseline CD4, 2 which may contribute to the poor CD4 recovery of these patients. Continued engagement with communities, particularly with men and older clients, is required to emphasise the importance of engaging with ART services before CD4 counts have dropped substantially.…”
Section: Discussionmentioning
confidence: 99%
“…1 Advanced clinical care is particularly important in South Africa, considering that up to 40% of adults initiate ART with CD4 < 200 cells/mm 3 . 2 Furthermore, up to 50% of patients receiving ART demonstrate poor CD4 recovery, dependant on multiple factors including baseline CD4 count and CD4 recovery definition. 3 , 4 , 5 , 6 In some patients, known as immunological non-responders (INRs), CD4 count remains low despite a suppressed VL, which significantly increases the risk of mortality.…”
Section: Introductionmentioning
confidence: 99%